Using Cognitive Dissonance to Manipulate Social Preferences - Robert J. Oxoby; Alexander Smith (Institute for the Study of Labor (IZA), 2014)
We explore the role of cognitive dissonance in dictator and public goods games. Specifically, we motivate cognitive dissonance between one's perception of fair treatment and self-interested behaviour by having participants answer a question about fairness. Utilizing two manipulations (reminding participants about their answer to the fairness question and publicly reporting aggregate answers to the question), we find that there is greater cognitive dissonance and behavioural change when there is a social component (i.e., reporting of aggregate answers). When a participant's answer to the fairness question is private, there is less dissonance and hence no behavioural change.
Keywords: C91; D64; H41; 330; cognitive dissonance; experiments; social preferences